PENGARUH MOTIVASI DAN PELATIHAN TERHADAP KINERJA PERAWAT (Studi Kasus Perawat Rumah Sakit Islam Sultan Agung Semarang) - Kartika, Winda; Nugraha, Hari Susanta (Jurnal Ilmu Administrasi Bisnis, 2020)
This study aims to determine the effect of motivation and training on the performance of Nurses of Sultan Agung Islamic Hospital Semarang. The type of research described is explanatory research with the Systemic Random Sampling method as a sampling method. The study population was nurses at Sultan Agung Islamic Hospital Semarang and the study sample were 84 respondents. This study uses quantitative analysis with validity, reliability, correlation coefficient, coefficient of determination, simple and multiple regression, significance, t test and F test with SPSS 21 application. The results of this study indicate that there is a positive influence between motivation and training variables on nurse performance which means that if an independent variable increases in the dependent variable there will be an increase in the dependent variable. The correlation coefficient between the two independent variables with the dependent variable has a strong relationship. The amount of contribution owned by the motivation variable shows that both variables are able to explain and predict the dependent variable. The coefficient of determination of motivational variables is worth 27.1% and the coefficient of determination of training is worth 42.5%.